PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN DAN PENANGGULANGAN STUNTING DI KELURAHAN SETONO KECAMATAN PEKALONGAN TIMUR KOTA PEKALONGAN - Dewi Nugraheni Restu Mastuti; M. Adika Nggofur Rurrochim; Sinta Wulandari; Boy Galant Merpati Pura; Muflihatun Ni’mah; Siti Shifa Akmalia; Via Khabibatul Aulia (LPPM Universitas Pekalongan, 2023)
Cases in Indonesia are still very high with an average prevalence in 2021 of 24.4%. According to the results of the Indonesian Nutrition Status (SSGI) in 2021, 20.9% of children under five (toddlers) in Central Java are stunted, where for Pekalongan City it is ranked 18th out of 34 districts/cities in Central Java with stunting prevalence in toddlers. 20.6%, this figure is still far from the 14% target to be achieved in 2024. Interventions in efforts to reduce stunting rates in Setono Village are carried out by the community service team through 6 forms of intervention in community empowerment activities: 1) GENTING (Youth Movement) Prevent Stunting), 2) GOSTING (Stunting Gossip), 3) TEKAAT (Practice of Giving Healthy Snacks), 4) ISI (Giving MPASI), 5) NAMPOL CULTURE (Cultivation of Plants in Polybags), and 6) SOGIMIL CENTING (Socialization of Maternal Nutrition Pregnant Prevent Stunting), The results of the intervention activities that have been carried out are increasing public understanding about stunting, creating changes in parenting for toddlers for the better, and creating good nutritional food intake for toddlers in order to increase the level of public health as high as possible.Keywords: community service, community empowerment, stuntingÂ